Living in endemic area for infectious diseases accelerates epigenetic age. (October 2022) - Durso, D.F.; Silveira-Nunes, G.; Coelho, M.M.; Camatta, G.C.; Ventura, L.H.; Nascimento, L.S.; Caixeta, F.; Cunha, E.H.M.; Castelo-Branco, A.; Fonseca, D.M.; Maioli, T.U.; Teixeira-Carvalho, A.; et al.
Abstract: Inflammaging is a low-grade inflammatory state generated by the aging process that can contribute to frailty and age-related diseases in the elderly. However, it can have distinct effects in the elderly living in endemic areas for infectious diseases. An increased inflammatory response may confer protection against infectious agents in these areas, although this advantage can cause accelerating epigenetic aging. In this study, we evaluated the inflammatory profile and the epigenetic age of infected and noninfected individuals from an endemic area in Brazil. The profile of cytokines, chemokines and growth factors analyzed in the sera of the two groups of individuals showed similarities, although infected individuals had a higher concentration of these mediators. A significant increase in IL-1ra, CXCL8, CCL2, CCL3 and CCL4 production was associated with leprosy infection. Notably, elderly individuals displayed distinct immune responses associated with their infection status when compared to adults suggesting an adaptive remodelling of their immune responses. Epigenetic analysis also showed that there was no difference in epigenetic age between the two groups of individuals. However, individuals from the endemic area had a significant accelerated aging when compared to individuals from São Paulo, a non-endemic area in Brazil. Moreover, the latter cohort was also epigenetically aged in relation to an Italian cohort. Our data shows that living in endemic areas for chronic infectious diseases results in remodelling of inflammaging and acceleration of epigenetic aging in individuals regardless of their infectious status. It also highlights that geographical, genetic and environmental factors influence aging and immunosenescence in their pace and profile. Highlights: Inflammatory profiles, but not cytokine/chemokine levels, of infected and control individuals from endemic area are similar. Infected elderly from endemic area had distinct immunity if compared to adults suggesting remodeling in their inflammaging profile. Geo- environmental and genetic factors influence the senescence pace and individuals from the endemic areahad accelerated aging.